Teaching English Conversation Through Portfolios - . Budiawan (Bandar Lampung University (UBL), 2013)
This plain class action research explores the application of portfolio in English classroom setting, particularly advanced conversation. Students created portfolios about their friends’ presentations, which cover the contents of the presentations, grammatical errors, mispronunciations, and fluencies. In short, they assessed their friends’ performances. It shows that it can raise students’ critical thinking, motivations, as well as makes the class more lively, particularly in questions and answers session. In addition, it can be one of lecturer’s records in giving students final assessment.